International Law Non-Compliance: Assessing Uruguay’s Decision to Legalize Cannabis under Jose Mujica Regime - Tesalonika, Novia Sinta; Kusumawardani, Natasya (AEGIS : Journal of International Relations, 2018)
Uruguay has ratified the international drug control conventions that consist of Single Convention on narcotic drugs 1961 as amended 1972 protocol, the convention on psychotropic substance 1971, and United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances 1988. Since then, the Uruguayan government has been a part of the ‘War on Drugs" campaign. In 2012, Jose Mujica proposed the policy of cannabis legalisation. The proposal was signed and passed into Uruguay law no 19172 that allow and regulate the plant, consumption and sale of cannabis on December 20th, 2013. This policy has violated international drug control conventions and received critics from the International Narcotics Control Board (INCB), the body of the United Nations Office on Drugs and Crime (UNODC). Despite the critics from INCB, the government stood against the norm of the treaty. This article analyses the causative factors that trigger this behavioural change. The increasing number of drugs users caused many problems in Uruguay especially the increasing numbers of criminal acts. It created national problems and hampering the government's efforts to fight drug trafficking and ensuring the safety of society. By all mean, it became threats to their national interest. Thus, the government believed that compliance with the conventions could not help them to overcome these threats. Uruguay case has shown that state behaviour towards international law will change along its changing national interest.